Fragmentation of scheduled visits and missed doses among infants receiving multiple injected vaccines - Mark J. Person; Kerry Anne McKenzie; Fay Macartney-Bourne (Elsevier, 1997)
Abstract: A retrospective cohort study was used to determine the extent to which immunisation visits due in the first year of life are split into separate visits. A one-month birth cohort of infants registered in early childhood health centres in the former Eastern Sydney Health Area was followed up when the infants were 8 to 11 months of age. A telephone questionnaire sought documented dates of each dose in the primary series of diphtheria-tetanus-pertussis (DTP), Haemophilus influenzae type b (Hib) and hepatitis B (HBV) vaccination. Of the 141 subjects, 130 had received all due doses of DTP and Hib vaccines and 63 (45 per cent) had been enrolled in the neonatal hepatitis B program. Infants in the latter group received the first DTP-Hib dose on average one week later than did those not in the hepatitis B program (DTP, P= 0.016; Hib, P= 0.047). The greatest percentage of missed DTP or Hib doses occurred in infants not receiving HBV vaccination (7.1 per cent of doses) or those high-risk infants enrolled in the neonatal hepatitis B program (2.9 per cent). Overall, 12 infants had 28 (6.9 per cent) of the 404 possible scheduled visits fragmented into two separate visits. In all cases, parents reported that this was at the suggestion of the general practitioner. We found no greater likelihood of fragmentation for infants who had also received hepatitis B vaccine. Only 17 infants (29 per cent) had received the third hepatitis B vaccine and DTP doses at the same visit, as recommended. These findings confirm anecdotal reports of fragmentation of scheduled visits and missed doses for infants due to receive multiple injections, and some delay in uptake among those receiving hepatitis B vaccine. Universal infant hepatitis B immunisation should not be considered until combination vaccines (which should also include a Hib component) become available in Australia.